THE CONCEPT OF LIMIT, LIMIT OF A FUNCTION, AND CONTINUITY OF A FUNCTION - Kamalova Hillolakhan Solijonovna (Western European Studies, 2024)
This paper delves into the fundamental concepts of limits, limit of a function, and continuity of a function in calculus. It provides a comprehensive overview of these concepts, their definitions, properties, and their significance in mathematical analysis. Through examples and discussions, the paper aims to enhance understanding and application of these concepts in various mathematical and scientific contexts
Keywords: limit; limit of a function; continuity